Arterial stiffness and the risk of heart failure formation in rotational shift workers in the arctic. (14th October 2021) - Shurkevich, N; Vetoshkin, A; Gapon, L; Dyachkov, S; Simonyan, A
Abstract: Aim: To investigate factors associated with arterial hypertension (AH) development, evaluate arterial stiffness (AS) and the risk of heart failure formation in rotational shift workers in the Arctic. Methods: Within 6 days of September 2019, in the polar settlement of Yamburg (68 N), on the basis of Yamburggazdobycha LLC medical unit, 183 individuals (48.7±8.3 years), working rotating shifts (16.9±8.7 years) were enrolled via medical examination. Patients were divided into 2 groups according to the level of blood pressure (BP): Group 1 (Gr. 1) included 86 individuals with AH of 1, 2 stages; Group 2 (Gr. 2) comprised 97 individuals with BP <140/90 mm Hg. Ultrasound examination of carotid arteries (CA) was performed, Peterson's elastic modulus (Ep), β-stiffness index, cardio-ankle vascular index (CAVI), pulse wave velocity (PWV) were determined; ABPM was performed; EchoCG was conducted using calculation of probability for heart failure with preserved ejection fraction (HFpEF) by the H2FPEF score (Heavy; Hypertensive; Atrial Fibrillation; Pulmonary Hypertension; Elder; Filling Pressure); blood lipid spectrum, inflammatory markers, brain natriuretic peptide were determined. Results: In Gr.1 vs Gr.2, elevated levels of left CAVI (7.9 vs 7.4) (p=0.022) and right CAVI (7.9 vs 7.5) (p=0.045) were registered; PWV: 13.8 m/s vs 12.6 m/s (right), (p<0.001) and 13.9 m/s vs 12.6 m/s (left), (p<0.001); triglycerides, (p=0.03); very low density lipoprotein cholesterol, (p=0.054); homocysteine, (p=0.025). Probability of HFpEF by the H2FPEF score was higher in Gr.1 than Gr.2 (p<0.001). According to logistic regression analysis, data of odds ratio (OR) determined the risk of AH developing with increasing of PWV (OR=1.444); 24-hour diastolic blood pressure variability (DBPV24) (OR = 1.164); probability of HFpEF by the H2FPEF score (OR = 1.677). Relationships of Peterson's elastic modulus (Ep) of common carotid artery (CCA) with left ventricular myocardial mass (LVMM) (r=0.39), (p<0.01), LVMMI (r=0.39), (p<0.01), probability HFpEF by H2EPEF score (r=0.27), (p<0.01); β-stiffness index of CCA with LVMM (r=0.25), (p<0.01) were found. Conclusion: Interrelation of AH with PWV (OR=1.444), DBPV24 (OR=1.677), probability of HFpEF by the H2FPEF score (OR = 1.677) should be considered for prognostication of the risk of AH with HFpEF formation in rotational shift workers in the Arctic. Associations of AS with LVMM and LVMMI, HFpEF signs may indicate processes of simultaneous interconnected formation of arterial and cardiac stiffness. FUNDunding Acknowledgement: Type of funding sources: None.